KEMAMPUAN MAHASISWA MEMBACA TEKS ILMIAH PADA PROGRAM STUDI PENDIDIKAN BAHASA INDONESUA FKIP UNTAN PONTIANAK - Susilowati, Endang (Jurnal Pembelajaran Prospektif, 2021)
This study was aimed at obtaining a deep understanding of the students' ability to read scientific texts, the obstacles they face, and how to overcome students’ difficulties of the second semester of the Indonesian Language and Literature Education Study Program in 2020 of FKIP Untan Pontianak. The results of the students' ability to read scientific texts are used as teaching policies in an effort to motivate and increase students in reading scientific texts to make thembetter. The method used in this research was descriptive, a form of quantitative research. The data of this research ere the test results of the ability to read scientific texts regarding literal understanding, interpretation, evaluation, and understanding of appreciation. Sources of data in this study were students of the Indonesian Language and Literature Education Study Program, semester II of 2020, FKIP Untan Pontinak. Data collection tools were objective test questions on reading comprehension and content interpretation. The data analysis usedquantitative descriptive techniques. The validity of the data was done by checking the validity of the data and it was proven by the triangulation proposed by Robin and Meleong. The reliability of the ability to read scientific texts was determined by the reliability of the rating results. Based on the research results, it can be concluded that the students' ability to read scientific texts hadan average value of 74.46. This study covered 30 students. There were 22 students with good grades above 70. There are 8 students whose grades were below 70 or not good. The obstacles faced by students in reading scientific texts were students who were not accurate in answering questions 26.6%, who did not master the vocabulary of absorption elements 27%, who did not understand the meaning of words based on the context of written sentences 30%. Students who did not master the meaning of foreign loan words, 23%, were less able to interpret meanings and read evaluatively 27%. The solutions and suggestions given to overcome these obstacles were as follows: Students are trained to read comprehension critically, to look for difficult vocabulary elements of foreign language absorption, to explain their meaning and use them in the context of other sentences, to assess evaluative reading both in groups and individually.Students also need to take the initiative to learn on their own even though they are not assigned /supervised by lecturers.